A Bayesian Meta-Analysis and Systematic Review On Global And Local Prevalence Of Hepatitis B - Mohammad Haroon Khan, Shahid Hussain, Farhan Kamal Bakhtiar (International Journal of Scientific Research and Management (IJSRM), 2014)
Background: HBV is a global threat, more prevalent in Asia, Latin America, Africa and southern Europe. Pakistan is one of most prevalent countries with approximately 9 million infected. Researchers are trying to investigate the HBV prevalence worldwide but it is too expensive and time consuming to investigate a disease in millions of population.